Desenvolvimento e caracterização de um enxaguatório bucal fitoterápico para tratamento de candidose bucal - Figueirêdo Júnior, Ernani Canuto (2021)
Oral candidiasis is the most common fungal infection of the buccal cavity, whose therapy includes antifungal agents that have several toxic and side effects, pointing to the need to discover new strategies for its treatment. The aim of this study was to characterize the extract of Syzygium cumini (L.) Skeels (popularly known as jambolão), evaluate the pharmacological and toxicological potential of some of its compounds and develop a herbal mouthwash containing the S. cumini extract (HMSc), characterize and evaluate its antifungal activity in vitro. The methodology was conducted through the performance of magnetic resonance tests, thermal analysis and pharmacological and toxicological tests in silico in the extract, in addition to the development of the HMSc and performance of thermal analysis tests, accelerated and late stability and evaluation of minimum inhibitory concentrations (MIC), minimal fungicide (CFM) and growth kinetics of C. albicans.Data were presented through descriptive analysis, and the stability and growth kinetics tests were inferentially evaluated using the ANOVA test and Tukey's post-tests, with α=0.05. The results suggest that the extract has mostly phenolic and terpenoid compounds and has thermoanalytical parameters consistent with its quality controls, being these same aspects found for the HMSc. The substances evaluated in silico were active for most of the activities tested, being all of them compatible with oral bioavailability. As for bioactivity, the molecules showed different predictive categorizations. In addition, none of them have ADMET (Absorption, distribution, metabolism, excretion and toxicity) toxicity, but only hexadecanoic acid, ethyl ester, had systemic carcinogenic effects. As for acute oral toxicity, the substances fall into different categories (II to IV).The accelerated and late stability tests of the HMSc showed that its organoleptic characteristics remained unchanged and the density was stable in the different cycles/time intervals evaluated. In accelerated stability, the pH changed, showing a statistically significant difference only in the first cycles and it maintained compatibility with the skin pH and with the critical pH of dental demineralization in most of the cycles evaluated. In the late stability tests, this parameter remained stable and compatible with skin pHs and the critical pH of tooth demineralization. In in vitro microbiological tests, HMSc demonstrated an active antimicrobial potential on most Candida spp. strains, with MIC values between 39,0625 to 1.250,0 μg/mL and CFM of 625,0 μg/mL and ≥1.250,0 μg/mL, according to the strain tested and showing fungistatic action (MFC/MIC ≥ 4) on most strains tested. As for the effects on the growth kinetics of C. albicans, HMSc proved to be fungistatic with a statistically significant inhibitory effect on its growth, when compared to the negative control, especially against exposure to HMSc in a period ≥ 4-6 hours. Thus, the results seem promising regarding the possibility of a future indication and/or use of this formulation in the dental clinic for the treatment of oral candidosis.